Migration distance and breeding latitude correlate with the scheduling of pre-alternate body moult: a comparison among migratory waders - Lourenço, P.M.; Piersma, T. (Journal of Ornithology, 2015)
Moult is an important maintenance activity that should be carefully timed within the annual cycle. Many birds perform a pre-alternate moult of body feathers some time prior to the breeding season. In migrants, the timing of the pre-alternate moult coincides with the migration from wintering to breeding areas. In this study, we used visual plumage scores collected on the Continental Black-tailed Godwit Limosa limosa limosa in Portugal and The Netherlands to establish that the pre-alternate body moult of these birds during the northward migration between West Africa and The Netherlands takes place only in staging areas in the Iberian peninsula from late January to late February. A comparison of the moult strategy of these godwits with that of 20 other migratory wader populations (13 species) revealed that the former had a rather uncommon moult schedule which was more characteristic of populations with rather short migrations that breed at lower latitudes. We argue that this unusual moult schedule can be explained by a combination of ecological opportunity and proximate and ultimate trade-offs (hormonal incompatibly and maximization of plumage quality vs. time spent on migration, respectively).